2021
DOI: 10.1186/s40104-021-00574-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of negative heterosis for growth traits in chickens revealed by genome-wide gene expression pattern analysis

Abstract: Background Heterosis is an important biological phenomenon that has been extensively utilized in agricultural breeding. However, negative heterosis is also pervasively observed in nature, which can cause unfavorable impacts on production performance. Compared with systematic studies of positive heterosis, the phenomenon of negative heterosis has been largely ignored in genetic studies and breeding programs, and the genetic mechanism of this phenomenon has not been thoroughly elucidated to date.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…On the other hand, Elshennawy et al [ 20 ] analyzed 1693 lambs data and reported that increase of Romanov blood from 25% to 50% had no significant change in mature weight, rate of maturity and instantaneous growth rates at 2, 6 and 12 months of age. Negative heterosis is connected with nonadditive genes and their oxidative phosphorylation [ 21 ] which cause unfavourable impacts on production performance of animals. Heterosis reduces in later generations after F1 due to segregation and recombination losses [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Elshennawy et al [ 20 ] analyzed 1693 lambs data and reported that increase of Romanov blood from 25% to 50% had no significant change in mature weight, rate of maturity and instantaneous growth rates at 2, 6 and 12 months of age. Negative heterosis is connected with nonadditive genes and their oxidative phosphorylation [ 21 ] which cause unfavourable impacts on production performance of animals. Heterosis reduces in later generations after F1 due to segregation and recombination losses [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, oxidative phosphorylation forms adenosine triphosphate (ATP) as a result of the transfer of electrons from NADH or FADH2 to O 2 by a series of electron carriers related to six genes namely ATP6V1A, UQCRQ, NDUFA8, NDUFV3, NDUFB3, and UQCRC2. This pathway is also correlated with body weight in Drosophila, and is associated with heterosis in plants (Mcdaniel and Grimwood, 1971; Katara (Mai et al, 2021). The liver is the major site of amino acid metabolism and fat deposition in the body, and 37 non-conserved AS genes are significantly enriched in metabolic pathways, amino acid metabolism, and glycerolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is also correlated with body weight in Drosophila, and is associated with heterosis in plants ( Mcdaniel and Grimwood, 1971 ; Katara et al, 2020 ). By detecting ATP content and ATPase activity in reciprocal cross chickens, Mai et al validated that oxidative phosphorylation is the major genetic and molecular factor in growth ( Mai et al, 2021 ). The liver is the major site of amino acid metabolism and fat deposition in the body, and 37 non-conserved AS genes are significantly enriched in metabolic pathways, amino acid metabolism, and glycerolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, transcripts with class code “i”, “u” and “x” were retained. Subsequently, the sequence of known lncRNAs were download from two lncRNA databases, Domestic-Animal LncRNA Database (ALDB) ( 12 ) and NONCODE ( 27 ). We then used BLAST to align the unannotated transcripts to known lncRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptional changes in hybrids generally associated with processes involved in the energy production, metabolic rates, stress response and hormone signaling (10). In chickens, multiple studies illustrated the heterosis mechanism of important traits at different stages through genome-wide expression analysis of brain, liver and muscle (11)(12)(13). Long non-coding RNAs (lncRNAs) are pivotal epigenomic factors, a class of endogenous more than 200 bases in length, and could affect gene expression by acting as cis-or transregulators (14).…”
Section: Introductionmentioning
confidence: 99%